Health Checkup-The Changing State of Health Centres in North India - Jean Drèze; Reetika Khera; Rishabh Malhotra (EPW, 2024)
Contrary to a common narrative whereby public health services in India have “collapsed,” there is a general pattern of improving quality and utilisation over time. The pace of improvement, however, is far from adequate.
Keywords: Health insurance; PMJAY; Universal health coverage